If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2a + -12 = a + 12 Reorder the terms: -12 + 2a = a + 12 Reorder the terms: -12 + 2a = 12 + a Solving -12 + 2a = 12 + a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-1a' to each side of the equation. -12 + 2a + -1a = 12 + a + -1a Combine like terms: 2a + -1a = 1a -12 + 1a = 12 + a + -1a Combine like terms: a + -1a = 0 -12 + 1a = 12 + 0 -12 + 1a = 12 Add '12' to each side of the equation. -12 + 12 + 1a = 12 + 12 Combine like terms: -12 + 12 = 0 0 + 1a = 12 + 12 1a = 12 + 12 Combine like terms: 12 + 12 = 24 1a = 24 Divide each side by '1'. a = 24 Simplifying a = 24
| -5c+1=-24 | | 2a+12=a+12 | | 3q^2-5q-6q^2+3q= | | 3x+17=21-5x | | 0.07x+x=6981.61 | | 0.7x+x=6981.61 | | 12x^3+2x^2-3x=0 | | 0.2x=7 | | 3(z-5)=2z | | 2t-9=3(t+4) | | 6x+3x=8x+7 | | 0.007x+0.03=0.1 | | 6x+3x=18x+7 | | 8-b=13 | | 3b-5-6b-8=2x | | 2*(4x-6)+20x=-4*(8-2x) | | -2(y+4)=2 | | 2*(4x-6)+20=-4*(8-2x) | | 3x-11=-6+16 | | 9x^2+37x-46=0 | | 9(-7)-3y=-63 | | 9x-3y=-63 | | 24(b-1)+21=3(8b-1) | | 40+4y-16=-13y-12-3y | | 3y-2x=30 | | 3(n-6)=2n | | 6y+5x=30 | | 5x-6y=-35 | | 4x+3y=-28 | | 2+3x=13+x | | 5x-1=14-100 | | 19+3x=14+2x |